(untitled) (Research, Society and Development, 2019)
PIBID is a program that aims to encourage teaching and to qualify students who are interested in it. The program develops activities directed at basic education schools, and is performed together with teachers who are already in action with their practical and interdisciplinary experiences. It is also worth noting that the program is extremely important because it contributes to the improvement of the training of new teachers and also contributes to the valorization of the teaching career. The objective of the research is to show the difficulties encountered by the "Pibidians" in relation to the teaching of the physics discipline, and lead to an understanding of actions that could help to overcome such difficulties. This research is a case study with a bibliographical, methodological and qualitative approach. Its elaboration was preceded by methods of literature review, among them, the integrative review. It was concluded that the difficulties in the process of teaching learning with the discipline of Physics can be related to the contents and methodologies applied by the teachers in the classroom, where many of the times do not become easy to understand. And since physics is capable of bringing students to a reflection on the world of sciences under the prospect that it is not merely the fruit of pure scientific rationality; but above all, this science forms the student in a citizen way, physics provides the scientific production and at the same time the understanding of the knowledge needs of the universe and the phenomena that surround it. Finally, it is believed that poorly elaborated methodologies and content impede the significant role of physics in students’ lives.